2021
DOI: 10.1002/mgg3.1762
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic proximal trisomy 13q and regular trisomy 13 in a female patient with long survival: Involvement of an incomplete trisomic rescue and a chromothripsis event

Abstract: Background Trisomy 13 or Patau syndrome has a prevalence of 1:10,000–20,000 and is characterized by microcephaly, microphthalmia, polydactyly, as well as other dysmorphic features and malformations, with a patient survival of 13% in the first year. Trisomy 13 presents either as a free chromosome 13 trisomy or associated with a chromosomal Robertsonian translocation, as partial trisomy affecting proximal or distal 13q regions, and also as a mosaic. Mosaic trisomy 13 shows a highly variable phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…They reported that she could support her head and sit at eight months, could stand at one year and two months, and walk without help at two years of age. At the age of 12 years, she can say few monosyllabic words without an appropriate context [2]. In our case, the child was able to hold his head at two months, sit at seven months, and at the age of one year, he was able to stand and cruise around furniture by himself.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…They reported that she could support her head and sit at eight months, could stand at one year and two months, and walk without help at two years of age. At the age of 12 years, she can say few monosyllabic words without an appropriate context [2]. In our case, the child was able to hold his head at two months, sit at seven months, and at the age of one year, he was able to stand and cruise around furniture by himself.…”
Section: Discussionmentioning
confidence: 54%
“…At the age of six years, he can say two to three words phrases and knows numbers and colors. Morán-Barroso et al reported that pigmentary anomalies, like hyperpigmented and hypopigmented skin lesions, are present in 82% of patients with mosaic trisomy 13 [2]. No pigmentations or any type of skin lesions are present in the reported patient.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Trisomy 13, or Patau Syndrome, is a chromosomal aberration that results in an extra duplicate of chromosome 13 being present in the body cells. Trisomy 13 may be full trisomy 13 (a third copy of chromosome 13 exists in all cells), mosaic trisomy 13 (a third copy of chromosome 13 exists only in some cells), or partial trisomy 13 (only a partial third copy of chromosome 13 exists in all cells) [ 22 , 23 ]. Partial trisomy is typically only of the 13q type, meaning the extra copy present is that of the long arm (q) of chromosome 13 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 13 may be full trisomy 13 (a third copy of chromosome 13 exists in all cells), mosaic trisomy 13 (a third copy of chromosome 13 exists only in some cells), or partial trisomy 13 (only a partial third copy of chromosome 13 exists in all cells) [ 22 , 23 ]. Partial trisomy is typically only of the 13q type, meaning the extra copy present is that of the long arm (q) of chromosome 13 [ 23 ]. Furthermore, partial trisomy 13q is characterized by the presence of distinct symptoms including microcephaly, holoprosencephaly, leukoencephalopathy, facial anomalies, and intellectual disability [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%